LOV-based reporters for fluorescence imaging. (August 2015) - Buckley, Anthony M; Petersen, Jan; Roe, Andrew J; Douce, Gillian R; Christie, John M
Graphical abstract: Highlights: Flavin-binding LOV domains have been engineered as green fluorescent reporters. Several LOV-based FPs are available with different photophysical properties. LOV-based FPs can circumvent limitations commonly associated with GFP-related FPs. LOV fluorescence has been exploited for various imaging and biosensor applications. Their properties also offer new possibilities in cancer therapy and optogenetics. Abstract : Chromophore-binding domains from plant and bacterial photoreceptor proteins have recently gathered increasing attention as new sources of genetically encoded fluorescent proteins (FPs). In particular, FPs based on the flavin-binding LOV (light, oxygen, or voltage sensing) domain offer advantages over green fluorescent protein (GFP) owing to their smaller size, pH and thermal stability, utility under anaerobic conditions and their ability to generate reactive oxygen species. This review focuses on the potential applications of this emerging class of fluorescent reporters, discusses the advantages and limitations of LOV-based FPs, whilst offering insights regarding the further development of this technology for bioimaging and photodynamic therapy.